Evaluating the Effectiveness of Sister Province Cooperation: A Case Study in Yogyakarta and Gangwon-do - Aisyah, Adinda; Deniar, Shannaz Mutiara (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
Paradiplomacy has become an important phenomenon in international relations, especially for local governments. This study discusses the cooperation between the Yogyakarta Special Region Government and the Gangwon-do Government, South Korea, as an example of paradiplomacy in Indonesia. This study uses a qualitative descriptive method, with data collection through interviews, archival documents, and secondary sources. The results of the study show that cooperation between the Yogyakarta Special Region Government and the Gangwon-do Government has begun since 2008, with the signing of a LoI and followed by the signing of a MoU in 2009. This cooperation covers tourism, science and technology, education, agriculture, culture, and sports. However, the results of the study also show that the effectiveness of this cooperation still needs to be improved, especially in terms of coordination, strategy, and reporting systems. Therefore, this study recommends that local governments need to enhance their capabilities and capacities in managing international cooperation, as well as strengthen coordination and communication with the central government and international partners. This study also identified several gaps that need to be addressed, such as the lack of data and information on the implementation of cooperation, the lack of analysis on the impact of cooperation on local communities and economies, and the lack of evaluation of the effectiveness of cooperation. Therefore, this study recommends several future studies, such as analyzing the impact of cooperation on local communities and economies, proving cooperation's effectiveness, and analyzing cooperation's role and contribution in improving local governments' ability and capacity.